Uncertain Ontologies - Dianna Taylor (Foucault Studies, 2014)
This following essay explores the meaning and implications of philosophical critique and creativity within the work of Gilles Deleuze and Michel Foucault.  The two philosophers’ appeals to ontology, as an important site upon which their ethico-political commitments to critique and creativity simultaneously converge and diverge, frame this exploration.  The first part of the essay shows how Deleuze’s and Foucault’s respective ontologies further critique and creativity.  The second part of the essay focuses on a point of divergence in the two thinkers’ appeals to ontology: the relationship between philosophy and history.  From a Foucauldian perspective, the ahistorical character of Deleuze’s ontology of difference threatens to undermine its transformative potential, whereas from a Deleuzian perspective, the historical character of Foucault’s ontology of the present, while it may not undermine transformation, certainly does not facilitate it.  In conclusion, I argue that it is precisely from within these tensions that important, productive, and transformative aspects of Deleuze’s and Foucault’s work emerge.